Digital skills and course curriculum of the quantity surveying undergraduate programme in Malaysia - Sim, Yi Cheng (2021)
Construction industry had started to shift towards adopting digital technologies over the past decade. The transformation of construction industry will require new skill sets which ought to be embedded in the construction professional’s education. Higher education institutions shall prepare their students to acquire the crucial skills for their future employment. What are the digital skills required by quantity surveyors? What are the digital skills included in the course curriculum of quantity surveying undergraduate programme in Malaysia? This research aims to investigate the digital skills that had been imparted in the course curriculum of quantity surveying undergraduate programme in Malaysia. The objectives of this research are to review digital skills embedded in course curriculum of quantity surveying undergraduate programme in Malaysia; to examine the differences in the digital skill set acquired by quantity surveying students and graduates; to assess whether quantity surveying undergraduates and graduates differ in perception towards digital skills acquired and ought to be taught. Five digital skills are identified from the requirement of accreditation bodies and industry. The five digital skills are Data Collection, Data Processing, Data Analysis, Data Ethics and Data Privacy. The methodological choice of this research is mixed mode approach. Questionnaire survey is utilised to collect field data while course curriculum of Universiti Tunku Abdul Rahman quantity surveying programme is reviewed to assess the inclusion of digital skills in the quantity surveying courses. Data collected from 562 quantity surveying students and graduates are analysed quantitative and presented using both descriptive statistics and inferential statistics. The result revealed that quantity surveying students and graduates are more competent in Data Collection while less competent in Data Ethics. Besides that, quantity surveying students and graduates perceived that Data Analysis as the most important digital skill which shall be taught by their higher education institutions while Data Privacy is the least important digital skill. The research is expected to benefit the construction industry, regulatory bodies and quantity surveying higher education providers in improving the course curriculum of quantity surveying education programme to meet the demands of the Malaysian construction industry.